Post‐transplant plasmablastic lymphoma of the skin. (17th August 2012) - Black, Catherine L.; Foster‐Smith, Erwin; Lewis, Ian D.; Faull, Randall J.; Sidhu, Shireen K.
Abstract: Plasmablastic lymphoma (PBL) is a recently described rare variant of diffuse large B‐cell lymphoma characterised by its aggressive nature and plasmacytic differentiation. It most frequently arises in the oral cavity of human immunodeficiency virus (HIV)‐infected patients. However extra‐oral involvement is becoming increasingly recognised, particularly in HIV‐negative patients. We report a case of PBL presenting as multiple violaceous nodules and plaques on the leg of a HIV‐negative patient, 13‐years post‐renal transplant. To date, 20 cases of PBL presenting in the skin have been reported. We review and compare the clinico‐pathological features of these cases.